Separasi Steviosida dan Rebaudiosida A dari Crude Glikosida Daun SteviaRebaudiana Bertoni Menggunakan Resin Makropori - Eko Indra Permana; Judy Retti Witono; Andy Chandra (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Sugar consumption in Indonesia always increase every year. The increase of sugar demand cannot be fulfilled by the increase of sugar production. Low calories and low prices make food industry attracted to artificial sweeteners. The consumption of artificial sweeteners in excessive amount can lead to health problem. Stevia sweeteners can be used as the solution. The content of stevioside and rebaudioside A in stevia leaf make stevia sweeteners have a sweet taste, low calories and classified as safe. The purpose of this research is to determine the effect of stevia leaves type, separation method using resin, and dilution of stevia extract to separation rate (in %) of stevioside and rebaudioside A. Leaves types used in this research are stevia leaf cultivated in Unpar (leaf A) which is dried with microwave and leaf cultivated in Central Java (leaf B) which is dried with sunlight. Mass of Stevia leaves used is 10 grams. Separation methods that used are batch and continuous. Dilution of stevia’s extract used are 0, 5, 10, 25, and 50 times. Analysis performed in this research are total sugar analysis using anthrone method, analysis of stevioside and rebaudioside A content using HPLC, turbidity analysis using turbiditimeter, color analysis using colorimeter, and gravimetry analysis. The results showed that leaf A with batch method and 50 times dilution give the highest separation rate.